“The Maqāṣid Are the Qibla of the Jurists”: A Critical Analysis of Contemporary References to and Usages of Abū Ḥāmid Al-Ghazālī’s Dictum - Kepplinger, Eva (Religions, 2024)
Modernity reveals an intense preoccupation with the Intentions of the Sharia (maqāṣid al-sharīʿa) and reflections of premodern scholars on this legal concept. Within contemporary research in this field, the famous scholar Abū Ḥāmid al-Ghazālī (d. 505/1111), who is counted among the pioneers of premodern contributions to the maqāṣid, occupies a special position. In addition to his general treatment of the maqāṣid, one dictum of his in particular is often referred to in the modern literature on the maqāṣid. The quotation reads: “The maqāṣid are the qibla of the jurists”, which he mentioned in his book Kitāb Ḥaqīqat al-qawlayn and is indicative of the central position of the maqāṣid in al-Ghazālī’s (legal) thought. My investigation of the contemporary, primarily Arabic, literature on the maqāṣid which cites this popular dictum reveals that the quote is used for many reasons and in various contexts; however, a fuller engagement with the quote itself and in the context of al-Ghazālī’s thought, as well as in his book, takes place very rarely, if at all, and even then, it is cursory. In order to embed al-Ghazālī’s dictum in the wider frame of his thought, this article first presents his general maqāṣid-related thought and consequently expounds on it in the context of his book. To better understand the usage of the quote in modern scholarship, the current maqāṣid literature that refers to the dictum is analyzed and categorized, showing how authors deploy it and to what end.
CRIS-Team Scopus Importer:2024-03-08
Keywords: Abū Ḥāmid al-Ghazālī; Kitāb Ḥaqīqat al-qawlayn; maqāṣid; modern legal literature; modern references to al-Ghazālī´s dictum